Bullying dalam Perspektif Islam Pembelajaran dari Al-Quran dan Hadits - Zuhur Diana; La Zubair; Ibrahim Maulana Rasyid Nur Ala (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
Phenomenon bullying is widespread in various aspects of life, especially among school-aged children. Case bullying which is increasing every year, which has a negative impact on the victims, perpetrators and witnesses involved. To reduce the number of acts of violence bullying requires various strategies, both preventive and repressive, that must be carried out by educational institutions. This research uses a qualitative approach method with library study data collection techniques (library research), namely collecting relevant information from various sources and analyzing it to obtain a credible and comprehensive theoretical study. The research results show that bullying is an act of intimidation or violence carried out by an individual or group to physically or psychologically injure the victim with an element of intention. In the Islamic view, bullying is a disgraceful act as stated in the QS. al-Hujurat verse 11 which emphasizes the prohibition of degrading other people because humans have no right to judge other people on any basis. The strategies for overcoming bullying in schools from a counseling and education perspective include: 1) providing education about bullying, 2) establish strict related rules bullying, 3) being a good role model, 4) providing support to the victim, 5) helping the perpetrator to stop, and 6) detecting the act bullying since early stage. Meanwhile, the strategies offered by Islam include: 1) patience and forgiveness (ta’limus shobri wal ‘afwu), 2) reconcile each other (al-ishlah), 3) grow self-confidence, and 4) al-mauidzah al-hasanah.